2017
DOI: 10.1038/srep45544
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for non-destructive determination of hair photo-induced damage based on multispectral imaging technology

Abstract: Extended exposure to sunlight may give rise to chemical and physical damages of human hairs. In this work, we report a novel method for non-destructive quantification of hair photodamage via multispectral imaging (MSI) technology. We show that the multispectral reflectance value in near-infrared region has a strong correlation with hair photodamage. More specifically, the hair segments with longer growing time and the same hair root segment after continuous ultraviolet (UV) irradiation displaying more severe p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…The photographs of the hair samples before and after UV irradiation are shown in Figure A. SEM analysis clearly demonstrated that this exposure time is sufficient to damage the hair (Figure B). Damage upon both UVA and UVB irradiation was visible in the outer layer of both blond and naturally brown hair samples (Figures B and S12). This effect was visible even in the case of hair treated with a commercial broad-spectrum hair sunscreen prior to irradiation (Figure S12), indicating that repetitive application of the sunscreen is a fundamental requirement for efficient photoprotection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photographs of the hair samples before and after UV irradiation are shown in Figure A. SEM analysis clearly demonstrated that this exposure time is sufficient to damage the hair (Figure B). Damage upon both UVA and UVB irradiation was visible in the outer layer of both blond and naturally brown hair samples (Figures B and S12). This effect was visible even in the case of hair treated with a commercial broad-spectrum hair sunscreen prior to irradiation (Figure S12), indicating that repetitive application of the sunscreen is a fundamental requirement for efficient photoprotection.…”
Section: Resultsmentioning
confidence: 99%
“…In hair, melanin absorbs a large fraction of incident radiation and also captures many of the free radicals generated from UV radiation absorption by amino acids, preventing the transport of these free radicals into the keratin matrix. , The extent of hair damage depends upon the nature of the hair pigments, with dark hair being more photostable than blond hair. This derives from the protective action of the melanin-rich cortex in the black hair, which shows only a slight modification of fiber proteins under irradiation . However, since the majority of melanin pigments in the hair are located in the inner cortex, and since penetration into the hair layers reduces radiation intensity, damage can occur only after prolonged exposure, and most damage occurs primarily in the outer cuticle. , Owing to the intense UV absorption of hair coated with PDA, we reasoned that synthetic melanin deposition on the hair could mitigate photodamage by shielding the covered outer hair layers from UV radiation. To date, the majority of reported biochemical and photochemical changes caused in hair by radiation exposure focuses on evaluation of physical changes to the outer components of hair anatomy. ,, As a validation, we investigated the effects of developed melanin coatings on morphological and optical changes of the outer hair layers upon UV irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro hair washing and exposure to visible light and UV light has been shown to damage hair, reducing the tensile strength of the hair and damaging the protective cuticle [20][21][22]. Increased photodamage in distal hair segments compared to proximal segments was described by Cao et al and the same pattern of damage could be reproduced by exposing hair from the proximal segment to increasing amounts of UV light [23].…”
Section: Discussionmentioning
confidence: 81%
“…shown to damage hair, reducing the tensile strength of the hair, and damaging the protective cuticle [108][109][110]. Increased photodamage in distal hair segments compared to proximal segments was described by Cao et al and the same pattern of damage could be reproduced by exposing hair from the proximal segment to increasing amounts of ultraviolet light [111]. In summary, the available data points in two directions, both supporting an increased loss of hormones in distal segments due to "wear and tear" of the hair.…”
Section: Increasing Testosterone Concentrations In Distal Hair Segmentsmentioning
confidence: 76%